2021
DOI: 10.1128/aem.02052-20
|View full text |Cite
|
Sign up to set email alerts
|

Regulator RcsB Controls Prodigiosin Synthesis and Various Cellular Processes in Serratia marcescens JNB5-1

Abstract: Prodigiosin, a red linear tripyrrole pigment normally secreted by Serratia marcescens, has received attention for its reported immunosuppressive, antimicrobial and anticancer properties. Although several genes have been shown to be important for prodigiosin synthesis, information on the regulatory mechanisms behind this cellular process remains limited. In this work, we identified that the transcriptional regulator RcsB encoding gene BVG90_13250 (rcsB) negatively controlled prodigiosin biosynthesis in S. marce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…More details on the regulation of prodigiosin by slyA are still unknown. RcsA was a positive regulatory gene of prodigiosin production in this study, which was accordance with the recent study in S. marcescens JNB5-1 (Pan et al, 2021). Some mutants with genes encoding membrane proteins inserted showed significantly decreased prodigiosin production.…”
Section: Discussionsupporting
confidence: 92%
“…More details on the regulation of prodigiosin by slyA are still unknown. RcsA was a positive regulatory gene of prodigiosin production in this study, which was accordance with the recent study in S. marcescens JNB5-1 (Pan et al, 2021). Some mutants with genes encoding membrane proteins inserted showed significantly decreased prodigiosin production.…”
Section: Discussionsupporting
confidence: 92%
“…S. marcescens , a part of the Enterobacteriaceae family of eubacteria, is found in a wide range of ecological niches and can produce many high-value secondary metabolites like prodigiosin ( 1 ), althiomycin ( 2 ), serratamolide ( 3 ). Besides the well-studied bacterial genes involved in the metabolic pathway of the secondary metabolites, a number of transcriptional regulator-encoding genes that play important roles in secondary metabolites synthesis in S. marcescens have also been investigated, such as regulator MetR ( 10 ), SpnR ( 11 ), CopA ( 12 ), CRP ( 13 ), HexS ( 14 ), RssB ( 15 ), RcsB ( 16 , 17 ), SmaR ( 18 ), EepR ( 6 ), PigP ( 7 ), GumB ( 8 ), RbsR ( 9 ), and RpoS ( 61 ) mediates prodigiosin production and regulator GumB ( 8 ), EepR ( 6 , 34 ), PigP ( 62 ) and HexS ( 7 ) regulation of serratamolide synthesis. However, our understanding of the regulatory mechanisms behind secondary metabolites synthesis in S. marcescens is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the metabolic regulation network of prodigiosin biosynthesis in S. marcescens have revealed that pigABCDEFGHIJKLMN genes were involved in the biosynthetic pathway of prodigiosin synthesis ( Supplementary Figure S1 ) ( 1 ). Also, it is reported that prodigiosin biosynthesis in S. marcescens was widely regulated by a number of transcription factors including positive regulators EepR ( 6 ), PigP ( 7 ), GumB ( 8 ) and RbsR ( 9 ), and negative regulators MetR ( 10 ), SpnR ( 11 ), CopA ( 12 ), CRP ( 13 ), HexS ( 14 ), RssB ( 15 ), RcsB ( 16 , 17 ) and SmaR ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Motility bioassays were performed as described by Fineran et al (2005b) and Pan et al (2021), with slight modifications. Overnight cultured Serratia sp.…”
Section: Bioassays Of Motility Bacteriostatic Activity and Exoenzymesmentioning
confidence: 99%